2002
DOI: 10.1159/000063899
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lichenoid Reaction to Imatinib (STI 571, Gleevec)

Abstract: Imatinib or STI 571 is a phenylaminopyrimidine derivative and a member of a new class of drugs known as signal transduction inhibitors. These compounds specifically inhibit the proliferation of v-abl- and bcr-abl-expressing cells and have recently been approved as treatment for chronic myeloid leukaemia (CML). Results have been promising, and imatinib may well be the best single agent for the treatment of CML in the near future. Here we report an erosive oral lichenoid eruption confined to the buccal mucosa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 10 publications
1
24
0
2
Order By: Relevance
“…Imatinib may emerge as the mainstay treatment for CML. To date, imatinib has been reported to cause maculopapular rash, exfoliative dermatitis [1], AGEP [3], erosive lichenoid reaction [4] and pityriasis rosea [5]. Most of the cutaneous side effects of imatinib seem to be dose related; we believe continued treatment with low doses of imatinib 400 mg/day (as in our patient) eventually results in resolution of the rash.…”
supporting
confidence: 52%
“…Imatinib may emerge as the mainstay treatment for CML. To date, imatinib has been reported to cause maculopapular rash, exfoliative dermatitis [1], AGEP [3], erosive lichenoid reaction [4] and pityriasis rosea [5]. Most of the cutaneous side effects of imatinib seem to be dose related; we believe continued treatment with low doses of imatinib 400 mg/day (as in our patient) eventually results in resolution of the rash.…”
supporting
confidence: 52%
“…94 Both cutaneous and oral lichenoid eruptions have also been reported from imatinib. [95][96][97][98][99] Development of a mycosis fungoideselike eruption has been reported in 2 patients. In one case, the eruption was treated with triamcinolone cream and hydroxyzine and subsided after 1 year on continued imatinib therapy.…”
Section: Multikinase Inhibitorsmentioning
confidence: 99%
“…A case of erosive oral lichenoid reaction has also been recently described. 12 Raanani et al, 13 Hasan et al, 14 and Tsao et al 15 also reported some cases of cutaneous acquired hypopigmentation. Konstantopoulos et al 16 described a case of typical PR associated with IM but the authors did not show the clinical figures and neither did they perform a skin biopsy or serological tests and/or PCR for HHV-6 and HHV-7.…”
Section: Discussionmentioning
confidence: 97%